Wideband tympanometry for evaluating middle ear function and hearing prognosis after endoscopic type I tympanoplasty - Ren, Xiaoqian; Xu, Yihang; Yang, Yijing; Zhang, Yueqi; Zhang, Kexin; Ma, Qinzhuo; Pan, Meiyi; Wang, Wei (Frontiers in Neurology, 2025)
ObjectiveTo investigate the value of wideband tympanometry (WBT) in assessing middle-ear function after endoscopic type I tympanoplasty, and to analyze postoperative changes in wideband absorbance (WBA), resonance frequency (RF), and air-bone gap (ABG) and their relationships with hearing recovery.MethodsForty-four patients (44 ears) with unilateral chronic otitis media who underwent endoscopic type I tympanoplasty and completed postoperative follow-up were retrospectively enrolled as the study group. The contralateral normal ears (44 ears) of the same patients served as the control group. Independent-samples t-tests were used to compare postoperative WBA and RF between the two groups, and paired t-tests were used to compare preoperative and postoperative ABG within the study group. Spearman’s rank correlation analysis was used to assess the relationships between postoperative WBA, RF, and ABG. In addition, postoperative WBA at 1000 Hz was compared between temporalis fascia and tragal perichondrium graft subgroups using independent-samples t-tests.ResultsCompared with controls, the study group showed lower mean WBA across 226–8,000 Hz, with an asymmetric M-shaped pattern. Between-group differences in mean WBA were statistically significant in the mid-low (500–1,000 Hz), mid-high (1000–4,000 Hz), and high (4000–8,000 Hz) bands and were most pronounced in the 1,000–4,000 Hz band, whereas the difference in the low-frequency band (226–500 Hz) did not reach statistical significance. The mean RF was significantly lower in the study group than in the control group (t = −2.225, p < 0.05) and was negatively correlated with mean postoperative ABG (r = −0.439, p < 0.05). In the operated ears, postoperative ABG was significantly reduced at all tested frequencies between 250 and 4,000 Hz, and WBA at 1000 Hz was negatively correlated with postoperative ABG at the same frequency (r = −0.347, p < 0.05).ConclusionWBT sensitively reflects changes in the mechanical properties of the middle ear after type I tympanoplasty. Reduced WBA at mid-to-high frequencies together with decreased RF indicates increased tympanic membrane mass and reduced stiffness. The negative correlation between WBA at 1000 Hz and postoperative ABG indicates that WBA at this frequency may serve as an objective predictor of postoperative hearing prognosis, providing a quantitative basis for clinical efficacy evaluation.